Rare Metal‐Free Photo‐Aerobic Intramolecular Dehydrogenative Cyclization Reaction towards Polycyclic Heteroarenes. Issue 20 (12th September 2016) - Yamaguchi, Eiji; Sudo, Yusuke; Tada, Norihiro; Itoh, Akichika
Abstract: We have achieved a rare‐metal‐free photo‐aerobic intramolecular dehydrogenative coupling reaction from two C—H bonds of indole with malonate. This catalytic system proceeded at room temperature under visible light irradiation with oxygen in the air as a terminal oxidant, and the cyclization products were obtained in good to excellent yields. Abstract :